Role of the disposition to technology in the evaluation of tangible and non-tangible elements of after sales services - Castillo, Rony (2019)
The After Sales Services acquired a preponderant role in the results generation for the companies and the client’s satisfaction. It is important to understand the different aspects of their management in order to have a continuous improvement of their performance. Based on these services, the present research analyzes the moderating role of customer disposition in technology in the causal relationship of after-sales services’ elements, both tangible and non-tangible, in the experiential value of the customers and their willingness to purchase in the future. The results show the favorable impact that a positive performance of these resources has on the provision of these services for people with a high disposition towards technology. Given that the traditional elements of services, in general, and after-sales, in particular, are going to lose their relevance due to the emergence of the digital revolution technology, this research assesses how the elements of these services influence in the value of clients, focusing on how the disposition to technology regulates this link and has the potential to influence the final assessment of this relationship in the future.